Análisis de los procesos de atención hospitalaria y su impacto en los niveles de satisfacción - Noblecilla Piloso, Luis Alexander (2014)
This analysis focuses on the hospital care processes at the Health Sub-center at Pedro J. Montero parish and their impact on the levels of patient satisfaction. Hospital care services are in constant development in order to increase the rate of satisfaction and acceptance among patients attending third level healthcare entities known as Health Sub-centers. This study aims to determine factors that may have an impact on the dissatisfaction of the patients at the Health Sub-center, making this research a useful tool to improve these processes by analyzing positive and negative aspects of each one of the characteristics of the Health Sub-center. No records of previous studies on this matter have been found. The results show that the majority of patients have a basic knowledge of their healthcare benefits and that they believe the current administration is not entirely efficient due to specifically identified problems like the slowness in most care processes.